English Language Teacher Educator Interactional Styles: Heterogeneity and Homogeneity in the ELTE Classroom - Edgar Lucero; Jeesica Scalante-Morales (Asociación Colombiana de Profesores de Ingles, 2018)
This article presents a research study on the interactional styles of teacher educators in the English language teacher education classroom. Two research methodologies, ethnomethodological conversation analysis and self-evaluation of teacher talk were applied to analyze 34 content- and language-based classes of nine English language teacher educators of three undergraduate English language teacher education programs in Bogotá, Colombia. Findings show that English language teacher educators' interactional styles are a mixture of both individual (heterogeneous interactional styles) and common (homogeneous interactional styles) social acts, which are represented by the interactional forms and patterns that these teacher educators display in the classrooms.